Russian Federation : Report on the Observance of Standards and Codes-IOSCO Objectives and Principles of Securities Regulation. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2016)
This paper presents an assessment of the level of implementation of the IOSCO (International Organization of Securities Commissions) objectives and principles in the Russian Federation. Some of the most recent regulatory changes in the Russian Federation are clearly based on international standards. In other areas, further initiatives will be required. These include conflicts of interest identification and improving standards of management in professional market participants. It will also require the creation of legal gateways which will enable supervisors with the necessary skills sets to provide guidance as to what the Central Bank of the Russian Federation's (CBR) reasonable expectations are on a range of issues. CBR also faces a major challenge in enforcing the regulatory regime and will need additional resources.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet